2003
DOI: 10.1159/000068053
|View full text |Cite
|
Sign up to set email alerts
|

Extraventricular Intracisternal Obstructive Hydrocephalus – A Hypothesis to Explain Successful 3rd Ventriculostomy in Communicating Hydrocephalus

Abstract: The basis of successful 3rd ventriculostomy in cases of communicating hydrocephalus is not yet understood. We performed 3rd ventriculostomies in 5 patients with free cerebrospinal fluid (CSF) communication from the ventricles to the cisterna magna. Preoperative magnetic resonance images (MRIs) showed dilated ventricles, a downward bulging floor of the 3rd ventricle (interpreted as a sign of pressure gradient between the ventricles and basal cisterns) and a free communication to an enlarged cisterna magna. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 13 publications
4
33
1
2
Order By: Relevance
“…Although this assumption seems to be against traditional concept, a few case reports have been published with only 1 exit foramen of the fourth ventricle obstructed, causing tetraventricular hydrocephalus and responding to surgery. [23][24][25][26][27][28][29][30][31][32] These results overlap with observation in our large study cohort. The second step was the acquisition of the 3D-CISS sequence to determine whether there was obstructing membrane either within or outside the ventricular system.…”
Section: Mr Evaluationsupporting
confidence: 89%
See 1 more Smart Citation
“…Although this assumption seems to be against traditional concept, a few case reports have been published with only 1 exit foramen of the fourth ventricle obstructed, causing tetraventricular hydrocephalus and responding to surgery. [23][24][25][26][27][28][29][30][31][32] These results overlap with observation in our large study cohort. The second step was the acquisition of the 3D-CISS sequence to determine whether there was obstructing membrane either within or outside the ventricular system.…”
Section: Mr Evaluationsupporting
confidence: 89%
“…The membranes that obscured only the cisterns (ie, interpeduncular, prepontine, and premedullary) were defined as communicating hydrocephalus with cisternal obstruction. [22][23][24] The hydrocephalus was categorized as noncommunicating, even if one of the fourth ventricular outlets appeared obstructed while the others were patent. Although this assumption seems to be against traditional concept, a few case reports have been published with only 1 exit foramen of the fourth ventricle obstructed, causing tetraventricular hydrocephalus and responding to surgery.…”
Section: Mr Evaluationmentioning
confidence: 99%
“…Kehler et al showed that downward bulging third ventricular floors are associated with effectiveness of ETV treatment in cases of communicating hydrocephalus. 19 Bulging reflects the pressure gradient between the third ventricle and interpeduncular/prepontine cisterns. 20 In our patients, many with bulging third ventricular floors had prepontine membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been hypothesized that intact cistern flows around the brain stem and CMJ are essential to achieve ETV success. 20 Physiologically, the CSF that exits from the foramen of Magendie is directed to the cisterna magna. From the cisterna magna, the CSF travels superiorly into the subarachnoid space over the cerebellar hemispheres, and caudally into the spinal subarachnoid space and cephalad into the premedullary, prepontine, and interpenduncular cisterns.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Those CSF absorption devices declined possibly due to lengthy intracranial hypertension, especially in the patient with CSF diversion. 17,20,24 In other words, the previous ETV-treated OHCP might already coexist with "communicating HCP" due to the decrease in CSF absorption even before initial ETV.…”
Section: Discussionmentioning
confidence: 99%